Governing equations for acid water in canals - Dac, Nguyen Tat (Vietnam Journal of Mechanics, 1994)
It is given in this study governing equation system formulation for acid water movement in canals, especially, in the Plain of Reeds of Vietnam where the urbanite equilibrium is found dominant. It is assumed in the model a chemical equilibrium, however a kinetic treatment is also used to deal with dissolution of precipitates and sedimentation.